2019
DOI: 10.1111/geb.12870
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven convergent evolution of plumage colour in a cosmopolitan bird

Abstract: Aim The investigation of phenotypic diversity across geographical gradients is pivotal to understanding the evolution and adaptive functions of alternative phenotypes. The aim of the present study was to investigate whether the polymorphism in ventral plumage colouration observed in the cosmopolitan common barn owl group is determined by climatic factors, such as temperature and rainfall, consistent with Gloger’s and Bogert’s biogeographical rules. Location World. Time period 1809–2017. Major taxa studied Tyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 56 publications
(110 reference statements)
4
75
1
Order By: Relevance
“…Although the taxonomy of the common barn owl species complex has not yet been determined fully (Uva et al, ), all the phylogenetic analyses (Aliabadian, Alaei‐Kakhki, Mirshamsi, Nijman, & Roulin, ; Uva et al, ; Wink, El‐Sayed, Sauer‐Gürth, & Gonzalez, ) agreed that this group is split into three genetically distinct evolutionary lineages. Irrespective of their taxonomic level, from an evolutionary perspective these lineages can be considered as adaptive radiations occurring simultaneously in geographically separated regions: (a) the Western barn owl ( T. alba ), occurring in Africa, the Arabian Peninsula, the Middle East and Europe up to Southern Scandinavia; (b) the American barn owl ( T. furcata ), living from Southern Canada to Patagonia, including throughout the Caribbean, Galapagos and Hawaiian islands; and (c) the Eastern barn owl ( T. javanica ), inhabiting the part of Asia south of the Himalayan plateau and Australasia, including Tasmania and all the archipelagos in the Pacific Ocean (for further details, see Romano et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the taxonomy of the common barn owl species complex has not yet been determined fully (Uva et al, ), all the phylogenetic analyses (Aliabadian, Alaei‐Kakhki, Mirshamsi, Nijman, & Roulin, ; Uva et al, ; Wink, El‐Sayed, Sauer‐Gürth, & Gonzalez, ) agreed that this group is split into three genetically distinct evolutionary lineages. Irrespective of their taxonomic level, from an evolutionary perspective these lineages can be considered as adaptive radiations occurring simultaneously in geographically separated regions: (a) the Western barn owl ( T. alba ), occurring in Africa, the Arabian Peninsula, the Middle East and Europe up to Southern Scandinavia; (b) the American barn owl ( T. furcata ), living from Southern Canada to Patagonia, including throughout the Caribbean, Galapagos and Hawaiian islands; and (c) the Eastern barn owl ( T. javanica ), inhabiting the part of Asia south of the Himalayan plateau and Australasia, including Tasmania and all the archipelagos in the Pacific Ocean (for further details, see Romano et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we used > 7,600 specimens of the three distinct evolutionary lineages of this species complex, representing their entire range of distribution. Although their taxonomic status has yet to be elucidated fully (see Section 2.1), they can be considered as adaptive radiations occurring in different geographical regions and producing a large variety of local adaptations (see details described by Romano, Séchaud, Hirzel, & Roulin, ; Uva, Päckert, Cibois, Fumagalli, & Roulin, ): the Western (or Afro‐European) barn owl, T. alba , the American barn owl, Tyto furcata , and the Eastern (or Australasian) barn owl, Tyto javanica . The investigation of this model system therefore provides the unique opportunity to compare traits among populations exposed to very different climatic and ecological conditions, and to disclose whether the same abiotic factors promoted the evolution of convergent traits in geographically separated regions.…”
Section: Introductionmentioning
confidence: 99%
“…2018a; Romano et al. 2019). Constantin Gloger (1833), a pioneer of this type of research, observed that coloration in birds varied with local climatic conditions (Delhey 2019).…”
Section: Figurementioning
confidence: 99%
“…A white plumage might compromise camouflage during the daytime, particularly against harassing competitors, such as carrion crows, Corvus corone . There may also be added benefits of displaying a redder plumage, particularly in harsh conditions when a higher melanin feather content may increase protection against feather abrasion, humidity, and/or cold temperatures 59 . Thus, the hunting-related benefits of a white plumage may trade off against survival to some extent.…”
Section: Discussionmentioning
confidence: 99%